Impact of after-pulse, pixel crosstalk and recovery time in multi-pixel photon counter (TM) response - Ward, M; Vacheret, A (2009)
The photon detection efficiency (PDE) and response linearity of Multi-Pixel Photon Counter (MPPC) is presented at 470 and at 500 nm coupled with wavelength shifting fibre. It is found that crosstalk and after-pulse increase artificially the PDE as much as 30% (relative). PDE increase with gain is found to be 2.5 % / 105. An empirical fit based on simple statistical assumptions is being developed and allows for some prediction of the fraction of nuisance parameters in the linearity response although experimental conditions are not completely modelled and are in the process of being tuned using a Monte Carlo simulation. © 2009 Elsevier B.V. All rights reserved.